Temporary Mate Removal During Incubation Leads to Variable Compensation in a Biparental Shorebird - Bulla, Martin; Valcu, Mihai; Rutten, Anne L.; Kempenaers, Bart (Frontiers in Ecology and Evolution, 2019)
Theoretical models predict that parents feeding offspring should partially compensate for the reduced care of their partner. However, for incubating birds, the level of compensation may depend on how reduced care changes the risk of entire brood failure, for example due to clutch predation, and on individual variation in the timing of depletion of energy stores. Although biparental incubation dominates in non-passerines, short-term manipulations of care during incubation are scarce. Here, we describe the response of 25 semipalmated sandpipers (Calidris pusilla) to an unexpected ~12-hour absence (experimental removal) of their partner in the middle of the 21-day incubation period. During the period when the removed partner would have taken over to start its regular ~12-hour incubation bout, parents compensated partially for the absence of their partner’s care (mean: 59%). However, individuals varied in their response from no to full compensation, independent of parental sex. In contrast to incubation in undisturbed nests or by uniparental species, nest attendance of compensating parents tended to be higher during the warmer part of the day. Whereas compensation was unrelated to before-experimental share of incubation, parents that left the nest from a further distance upon human approach (more aware of or more ‘responsive’ to their environment) compensated more. The quality of incubation in the after-experimental period, i.e. after return of the partner, was lower than usual, but improved quickly over time. In seven nests where the removed parent never returned, the widowed partner attended the nest for 0-10 days (median: 4), which suggests that widowed semipalmated sandpipers can adjust their incubation behavior to that observed in uniparental incubators. To conclude, our results indicate that biparental incubators are willing to tolerate a missed or irregular incubation bout of their partner and we speculate that all individuals would compensate fully, but that some fail because they deplete their energy stores, while others may be less responsive to or initially even unaware of the absence of their partner.